POLITENESS STRATEGIES IN CBS '60 MINUTES' INTERVIEW BETWEEN BARACK OBAMA AND STEVE KORFT REGARDING OSAMA BIN LADEN'S EXECUTION - Kemala, Dwitania (2014)
The study is aimed at investigating politeness strategies observed by Barack Obama in the interview with Steve Kroft in CBS '60 Minutes" regarding Osama bin Laden's execution. This study employed a qualitative research design which included quantification to compute the number of occurrences of the data. The data were obtained from a transcription of interview of Barack Obama in CBS official website. For the framework of analysis, the study applied politeness strategies proposed by Brown and Levinson (1978). The study reveals that Obama only observed 3 politeness strategies. Obama frequently observed negative politeness strategies in the interview with 22 occurrences from 38 occurrences. Hedges were the most frequent sub-strategy of negative politeness observed by Obama. Then, it was respectively followed by impersonalizing S and H, and the last were giving deference and nominalization. By observing negative politeness strategy and its sub-strategies Obama tried to distance himself to the interview to save his negative face. The second, Obama observed positive politeness strategies and off-records strategies. Frequency of both politeness strategies were 8 times. Positive politeness and its sub-strategies were observed in order to hide the truth, to convince and to share experience with the interlocutor. While, off-record strategy and its sub-strategies were observed in order to avoid FTA. Through the result above, it can be inferred that Obama tended to put him and the interlocutor on distance but he still wanted to show solidarity to the hearers by showing his appreciation.